Laparoscopic sleeve gastrectomy differentially affects serum concentrations of FGF-19 and FGF-21 in morbidly obese subjects - Haluzíková, D; Lacinová, Z; Kaválková, P; Drápalová, J; Křížová, J; Bártlová, M; Mráz, M; Petr, T; Vítek, L; Kasalický, M; Haluzík, M (Obesity (Silver Spring, Md.), 2013)
OBJECTIVE: Fibroblast growth factor (FGF)-19 and FGF-21 are novel metabolic regulators that improve insulin resistance and obesity in rodents. The aim of the study was to assess the effects of laparoscopic sleeve gastrectomy (LSG) on serum concentrations of FGF-19 and FGF-21 along with circulating bile acids and other relevant hormonal and biochemical parameters. DESIGN AND METHODS: Seventeen females with obesity undergoing LSG and 15 lean healthy females were included into the study. Anthropometric and biochemical parameters, serum concentrations of FGF-19 and -21, insulin, adiponectin, leptin, C-reactive protein, resistin, amylin (total), ghrelin (active), glucagon-like peptide 1 (GLP-1, active), glucose-dependent insulinotropic peptide (GIP, total), peptide YY (PYY, total), pancreatic polypeptide (PP), and bile acids, and mRNA expression of selected adipokines and inflammatory markers in bioptic samples of subcutaneous fat were assessed at baseline and 6, 12, and 24 months after LSG. RESULTS: LSG markedly decreased body weight, BMI, waist circumference, and insulin levels and improved systemic inflammation and lipid levels. FGF-19 concentrations increased and FGF-21 concentrations decreased after LSG along with increased adiponectin and decreased leptin, amylin, and ghrelin levels. GLP-1, GIP, PP, and circulating bile acids were not affected by LSG. PYY decreased significantly 24 months after surgery only. mRNA expression analysis in subcutaneous fat showed markedly reduced proinflammatory state. CONCLUSIONS: Our results indicate that increased FGF-19 and decreased ghrelin concentrations could have partially contributed to the improvement of systemic inflammation and some metabolic parameters after LSG, while changes of FGF-21 are rather secondary because of weight loss.
Keywords: Resistin; dospělí; fibroblastové růstové faktory; Female; ghrelin; adiponektin; C-Reactive Protein; Gastrectomy; Obesity, Morbid; Adult; Bile Acids and Salts; ženské pohlaví; obvod pasu; Leptin; Adiponectin; Fibroblast Growth Factors; lidé; podkožní tuk; glukagonu podobný peptid 1; peptid YY; žlučové kyseliny a soli; Subcutaneous Fat; messenger RNA; Insulin; Waist Circumference; RNA, Messenger; Weight Loss; amylin; Islet Amyloid Polypeptide; leptin; gastrektomie; prospektivní studie; Prospective Studies; žaludeční inhibiční polypeptid; Gastric Inhibitory Polypeptide; Insulin Resistance; index tělesné hmotnosti; hmotnostní úbytek; Pancreatic Polypeptide; inzulinová rezistence; Ghrelin; pankreatický polypeptid; Glucagon-Like Peptide 1; resistin; lidé středního věku; C-reaktivní protein; Peptide YY; Body Mass Index; inzulin; Middle Aged; morbidní obezita; Humans